Impacto do prolapso apical nos sintomas urinários e na qualidade de vida de mulheres com prolapso de parede vaginal anterior - Magalhães, Thaís Fontes de (2017)
Introduction: In women with pelvic organ prolapse (POP), urinary symptoms can be caused by anatomical distortion in surrounding organs. Objectives: We aimed to evaluate the impact of apical prolapse on urinary symptoms and on quality of life (QoL) in women with anterior wall prolapse. Methods: This case-control study took place in Urogynecology clinics. Women with both apical and anterior wall prolapse (Group 1; with Pelvic Organ Prolapse Quantification system, POP-Q, points Ba ≥ -1, Bp < -1 and C ≥ -1) were compared to woman with isolated anterior wall prolapse (Group 2; with POP-Q points Ba ≥ -1, Bp < -1 and C < -1) in relation to urinary symptoms assessed through clinical history, visualization of urinary loss during stress maneuvers on the physical exam, pad test result and International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF) score; while QoL was assessed through the King's Health Questionnaire (KHQ) and Medical Outcomes Study 36-item Short Form (SF-36) surveys. Statistical analyses were carried out with the Statistical Package for the Social Sciences (SPSS) version 20.0, through Pearson's chi-squared test and the Mann Whitney U tests for categorical and numerical data, respectively. P values <0.05 were considered significant. Results: Women in Group 1 had larger cystoceles, less stress urinary incontinence (SUI) symptoms, fewer daytime voids and more urinary hesitancy; as well as less frequent urinary loss during stress maneuvers on the physical exam, fewer positive pad tests and lower impact of UI measured by the ICIQ-SF than Group 2. Group 1 also showed better UI-associated QoL through the KHQ; however, there was no difference between groups in relation to general QoL using the SF-36. Conclusion: The presence of apical prolapse with point C ≥ -1 in women with anterior vaginal wall prolapse is associated to greater cystoceles, lower prevalence of SUI and greater prevalence of abnormal bladder emptying, as suggested by Petros' Integral Theory System for posterior zone defects. Apical prolapse associated with anterior wall prolapse results in better UI-associated QoL, but does not influence general QoL, when compared to women with isolated anterior prolapse. Keywords: Pelvic organ prolapse. Urinary incontinence. Quality of life.